2019
DOI: 10.3390/molecules24122271
|View full text |Cite
|
Sign up to set email alerts
|

Cinnoline Scaffold—A Molecular Heart of Medicinal Chemistry?

Abstract: The cinnoline nucleus is a very important bicyclic heterocycle that is used as the structural subunit of many compounds with interesting pharmaceutical properties. Cinnoline derivatives exhibit broad spectrum of pharmacological activities such as antibacterial, antifungal, antimalarial, anti-inflammatory, analgesic, anxiolytic and antitumor activities. Some of them are under evaluation in clinical trials. In the present review, we have compiled studies focused on the biological properties of cinnoline derivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…The complexity and wideness of this issue are documented by two review articles. The first is a comprehensive up-to-date review focused on cinnoline derivatives exhibiting a broad spectrum of pharmacological activities such as antibacterial, antifungal, antimalarial, anti-inflammatory, analgesic, anxiolytic, and antitumor [1], and the second one deals with the research and applications of nucleotide analogues, especially the second-generation bridged nucleic acids [2].…”
mentioning
confidence: 99%
“…The complexity and wideness of this issue are documented by two review articles. The first is a comprehensive up-to-date review focused on cinnoline derivatives exhibiting a broad spectrum of pharmacological activities such as antibacterial, antifungal, antimalarial, anti-inflammatory, analgesic, anxiolytic, and antitumor [1], and the second one deals with the research and applications of nucleotide analogues, especially the second-generation bridged nucleic acids [2].…”
mentioning
confidence: 99%
“…Dorofeenko et al demonstrated using 1 H NMR in CF3CO2H that 6-methoxy-1H-benzo[de]cinnoline 13 and its N-methyl derivative protonate on C7. 21 © ARKAT USA, Inc (10) with methyl and propyl iodides as well as with benzyl chloride in alkaline medium leads to the formation of the corresponding both N-substituted (11, 39, 40) and 9-substituted cinnoline derivatives (41,42) and also to the dimerization product (43) of the initial compound that corresponds to the formation of a N1-C9 bond (Scheme 3). 22 IR and 1 H NMR spectra were used to establish the structures; remember that protonation takes place at C7 while the alkylation occurs at C9.…”
Section: Acidity and Basicitymentioning
confidence: 99%
“…A mono doping of naphthalene with N at position 1 yields a quinolone molecule [ 19 , 20 ]. While cinnoline, quinazoline and quinoxaline are derived via di-doping of naphthalene with N atoms at positions 1 and 2, 1 and 3, and 1 and 4, respectively [ 21 , 22 , 23 , 24 ]. The inclusion of N atoms in the backbone of naphthalene chemically alters the electronic make-up, hence the emergence of new properties of interest.…”
Section: Introductionmentioning
confidence: 99%